2016
DOI: 10.1097/ccm.0000000000001673
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Resilience and Family Member Psychologic Symptoms in Critical Illness

Abstract: Objective There are increased rates of depression, anxiety, and stress disorders in families of critically ill patients. Interventions directed at family members may help their ability to cope with this stress. Specifically, resilience is a teachable psychological construct describing a person’s ability to adapt to traumatic situations. Resilience can inherently assist individuals to diminish adverse psychological outcomes. Consequently, we determined the relationship between resilience and symptoms of depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…This may be due to the fact that sons and daughters could not adapt to the critical situation (17). In contrast, Sottile et al (2016) found that resilience is not signi cantly related to gender (36).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This may be due to the fact that sons and daughters could not adapt to the critical situation (17). In contrast, Sottile et al (2016) found that resilience is not signi cantly related to gender (36).…”
Section: Discussionmentioning
confidence: 97%
“…Different results have been demonstrated bySottile et al (2016). They found that resilience is signi cantly associated with satisfaction from care and decision-making(36). Bailey et al (2010) did not nd either a signi cant correlation between perceived stress and satisfaction with care and decisionmaking(41).Only gender was found to be signi cantly associated with PSS-14 (p = 0.050).…”
mentioning
confidence: 90%
See 3 more Smart Citations